Situational Position and Student Choice Criteria - Church, H. John; Gillingham, David W. (Canadian Journal of Higher Education, 1985)
The student in choosing a particular university to attend does so within a particular university-student situational context. This paper demonstrates that the situational context significantly influences the evaluative criteria used by students in deciding which university to attend. Using a Canadian university as a case study, the authors develop an analytical framework for understanding the relationship between the particular university-student situational context and the student choice of university decision criteria.